Localization Design of the Traction and Network Control System for Standardized Subway - YI Rongwu; ZHOU Bin; WU Bin; CHEN Dong; LI Yi (Kongzhi Yu Xinxi Jishu)
With the continuous emergence of network and information security challenges, international trade frictions and other issues, the demand for localization, independence and controllability of products is becoming more and more intense. As a result, domestic hardware and software solutions will be gradually adopted to replace foreign solutions for the key control system in the field of rail transit. This paper briefly describes the architecture of the domestic traction and network control system for the standardized subway platform, and focuses on the selection of the hardware and software, such as CPUs, embedded operating systems and graphical development software. It also details the hardware scheme, software structure, and migration and adaptation process of the software and hardware for the traction and network control system, and makes a comparative analysis on the functions and performances of the domestic operating system and VxWorks. Through a series of software functional tests such as verification of traction/electric braking characteristics and networking, conclusions are drawn that the domestic traction and network control system features excellent performance parameters, stable and reliable operation, normal traction/electric braking characteristics, network delay of the system in microseconds, and jitter of the sub-microsecond level, which meet the requirements of the standardized subway platform, and therefore it can be used for 100% localization as an equivalent substitute.